"Metal-free'' synthesis of 1,2,3-triazoles via tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of ethyl acrylate derivatives - Kumar, B. Senthil; Gadakh, Sunita; Sudalai, Arumugam (Tetrahedron Letters, 2018)
An efficient ``one-pot'' method for the synthesis of substituted 1,2,3-triazole derivatives in excellent yields as single regioisomer is reported. The key transformation involves an atom-efficient tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of acrylate derivatives on treatment with NaN3 in DMF under mild conditions. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Intramolecular cycloaddition; Regioselective; Tandem azidation; triazoles